2015
DOI: 10.1021/es5051309
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning Behavior of Heavy Metals and Persistent Organic Pollutants among Feto–Maternal Bloods and Tissues

Abstract: Heavy metals and persistent organic pollutants (POPs), including Pb, Cd, T-Hg, MeHg, PCDD/Fs, PCBs, PBDEs, PCNs, and PBDD/Fs, were analyzed in 20 paired samples of cord blood, maternal blood, maternal urine, and placenta. The samples were collected from pregnant mothers and neonates from South Korea in 2010. The distribution of heavy metals among the samples varied with their physicochemical characteristics. The concentrations of Pb and Hg in the maternal and the cord blood samples were significantly correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 69 publications
4
31
3
Order By: Relevance
“…PCA has been used to a certain extent to quantify correlations among exposures to environmental chemicals (Frederiksen et al, 2009; Kim et al, 2015; Robinson et al, 2015); recently, PCA was used to assess patterns of exposure to biomarkers of phthalates, parabens, certain pesticides and BPA among young children (Myridakis et al, 2015,2016). For this group of 3–5 year olds, PCA suggested seven distinct principal components which described almost 75% of the variance.…”
Section: Discussionmentioning
confidence: 99%
“…PCA has been used to a certain extent to quantify correlations among exposures to environmental chemicals (Frederiksen et al, 2009; Kim et al, 2015; Robinson et al, 2015); recently, PCA was used to assess patterns of exposure to biomarkers of phthalates, parabens, certain pesticides and BPA among young children (Myridakis et al, 2015,2016). For this group of 3–5 year olds, PCA suggested seven distinct principal components which described almost 75% of the variance.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, numerous studies have examined the relationships of environmental contaminants, such as PBDEs, within maternal serum, umbilical cord blood, and placenta tissues. The results of these studies indicate that transplacental transfer (TPT) of PBDEs does occur, and leads to fetal exposure during gestation 3033 . For example, a study by Frederiksen et al found that PBDE exposure in the indoor environment, specifically from house dust ingestion, is linked to PBDE concentrations in maternal and umbilical cord plasma, which are additionally correlated with the PBDE concentrations measured in the paired placental tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is still possible that fine-scale differences in the lipid profiles between sexes may be driving these observed BFR bioaccumulation rates, and future research should utilize a lipidomic assessment of placenta tissue in order to fully characterize the lipid molecule profile of placental tissues. This is important because PBDEs have been shown to differentially bind to various classes of lipoproteins, and there may exist sex differences in the expression of placenta lipoproteins [49, 50]. One additional explanation of differences in BFR bioaccumulation rates may be that the placental tissue expression of TH transporting membrane proteins, including monocarboxylate transporters (MCTs), System-L amino acid transporters (LATs), and organic-anionic transport protein (OATPs), is sexually dimorphic.…”
Section: Discussionmentioning
confidence: 99%